A phase diagram approach to the detection and location of faulty capacitor units in A 115-kV capacitor bank based on unbalanced current arguments - Chaichan Pothisarn; Praikanok Lertwanitrot; Atthapol Ngaopitakkul (Heliyon, 2023)
The protection of traditional high voltage capacitor banks relies on an unbalance relay which operates when an internal fuse is blown. However, the unbalance relay cannot indicate cause or position of the fault. Thus, an operator wastes time and human resources investigating the fault issues. To address this issue, a method to locate the fault position in a capacitor bank is developed in this study. The study was simulated by using PSCAD software and modeled on the 115-kV system of the Electricity Generating Authority of Thailand (EGAT). Case studies involving faults with varied phases, side and branch connections, row connections, and inception angles were considered. Moreover, the magnitude and argument of the current phase and unbalanced current were analyzed to identify the fault location in a capacitor bank. The performance of the proposed method was verified via comparison with that of traditional methods and the results of laboratory experiments. In addition, various voltage systems were observed to verify the flexibility and accuracy of the proposed method. The results demonstrate that the proposed method was more efficient than traditional methods at locating the fault position in a capacitor bank.
Keywords: Power Systems Fault Detection; Power Transformer Diagnostics and Insulation; Power System Reliability and Maintenance